Integrated physical rehabilitation for patients with acute ischemic stroke - О. Е. Malneva; M. D. Selkin; A. E. Kutuzova; T. A. Evdokimova; N. A. Gomzyakova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article presents the results of comparison of different methods of rehabilitation in patients undergoing acute ischemic stroke, including those with cognitive disorders.